Metal–Organic Frameworks Meet Two‐Dimensional Materials in Polymer Matrices for Flame Retardant and Sensor Applications - Xue Bi; Yanan Hou; Ye‐Tang Pan; Siqi Huo; Congling Shi; Jiyu He; Rongjie Yang (Small Science)
Functional polymer composites offer versatility and high performance through material fusion, but flammability is an obstacle to application. Metal–organic frameworks (MOFs) have attracted attention in the field of flame retardant due to their structural diversity and high specific surface area, but they suffer from low efficiency and agglomeration issues when used alone. Combining with two‐dimensional (2D) nanomaterials can improve the above situation. Herein, strategies are explored for integrating MOFs with 2D materials through physical mixing and in situ growth to enhance their dispersion and flame‐retardant effects in polymers. Additionally, the integration of sensing performance can achieve intelligent monitoring and control, as well as real‐time risk assessment and system optimization. In summary, this review deeply analyzes the dispersion, interfacial interaction, and performance adjustment mechanism of composite materials and discusses in detail the application potential of MOFs and hybrids formed by 2D materials in the field of flame retardant and sensing. Finally, the opportunities and challenges faced by the integration of MOFs and 2D materials in functional polymer composites in the future are summarized and prospected. Herein, it is also expected to facilitate researchers to quickly understand the latest developments in the field and guide their effective design.